Swimming Training Modulates Nitric Oxide-Glutamate Interaction in the Rostral Ventrolateral Medulla in Normotensive Conscious Rats - Raquel, Hiviny de A.; Masson, Gustavo S.; Barna, Barbara Falquetto; Zanluqui, Nágela G.; Pinge-Filho, Phileno; Michelini, Lisete C.; Martins-Pinge, Marli C. (Frontiers in Physiology, 2016)
We evaluated the effects of swimming training on nitric oxide (NO) modulation to glutamate microinjection within the rostral ventrolateral medulla (RVLM) in conscious freely moving rats. Male Wistar rats were submitted to exercise training (Tr) by swimming or keep sedentary (Sed) for 4 weeks. After the last training session, RVLM guide cannulas and arterial/venous catheters were chronically implanted. Arterial pressure (AP), heart rate (HR) and baroreflex control of HR (loading/unloading of baroreceptors) were recorded in conscious rats at rest. Pressor response to L-glutamate in the RVLM was compared before and after blockade of local nitric oxide (NO) production. In other Tr and Sed groups, brain was harvested for gene (qRT-PCR) and protein (immunohistochemistry) expression of NO synthase (NOS) isoforms and measurement of NO content (nitrite assay) within the RVLM. Trained rats exhibited resting bradycardia (average reduction of 9%), increased baroreflex gain (Tr: -4.41±0.5 vs. Sed: -2.42±0.31 b/min/mmHg), and unchanged resting MAP. The pressor response to glutamate was smaller in the Tr group (32±4 vs. 53±2 mmHg, p<0.05); this difference disappeared after RVLM pretreatment with carboxy-PTIO (NO scavenger), Nw-Propyl-L-Arginine and L-NAME (NOS inhibitors). eNOS immunoreactivity observed mainly in RVLM capillaries was higher in Tr, but eNOS expression was reduced. nNOS gene and protein expression was slightly reduced (-29% and -9%, respectively, P>0.05). Also, RVLM NO levels were significantly reduced in Tr (-63% vs. Sed). After microinjection of a NO-donor, the attenuated pressor response of L-glutamate in Tr group was restored. Data indicate that swimming training decreasing RVLM NO availability and glutamatergic neurotransmission to locally administered glutamate may contribute to decreased sympathetic activity in trained subjects.